Determinants of Capital Structure the Case of Qatari Non-Financial Listed Companies - Ba-Abbad, Khaled Mohammed Abu Baker (2009)
A great deal of empirical research efforts have been carried out to provide empirical evidence on the determinants of capital structure choice. However, most of these efforts have been applied on companies listed on advanced stock markets The purpose of this study is to investigate whether the capital structure choice of Qatari companies can be explained by factors that have been found by previous studies as dominant determinants of capital structure choice (i.e., company size, company asset structure, company growth, and company profitability). The results reveal that among the variables, company size and profitability have dominant role in explaining the variation in the total debt ratios of Qatari companies. Meanwhile, company size, company assets' structure and company profitability have dominant role in explaining the variation in the long-term debt ratios of Qatari companies. However, only company size have dominant role in explaining the variation in the short-term debt ratios of Qatari companies